Severe Acute Respiratory Syndrome Coronavirus 2 and Male Reproduction: Relationship, Explanations, and Clinical Remedies - Xu, Jia; He, Liting; Zhang, Yuan; Hu, Zhiyong; Su, Yufang; Fang, Yiwei; Peng, Meilin; Fan, Zunpan; Liu, Chunyan; Zhao, Kai; Zhang, Huiping (Frontiers in Physiology, 2021)
Coronavirus disease 2019 (COVID-2019) caused by SARS-CoV-2 has been an ongoing pandemic and worldwide public health emergency, having drawn a lot of attention around the world. The pathogenesis of COVID-19 is characterized by infecting ACE-2-expressing cells, including testis-specific cells, namely Leydig, Sertoli, and spermatogenic cells, which are closely related to male reproduction. This leads to aberrant hyperactivation of the immune system generating damage to the infected organs. An impairment in testicular function through uncontrolled immune responses alert more attention to male infertility. Meanwhile, the recent clinical data indicate that the infection of human testis with SARS-CoV-2 may impair male germ cell development, lead to germ cell loss and higher immune cells infiltration. In this review, we investigated the evidence of male reproductive dysfunction associated with the infection of SARS-CoV-2 and its possible immunological explanations and clinical remedies.